The Influence of Principal Leadership on Teacher Performance with Work Motivation as a Mediating Variable in Public High Schools/Vocational Schools in Jepara Regency - Makrus; Agus Wahyudin (Universitas Negeri Semarang, 2026)
This study aims to analyze the effect of principal leadership on teacher performance with work motivation as a mediating variable in public senior high schools (SMA) and public vocational high schools (SMK) in Jepara Regency. This study uses a quantitative approach with a survey method. The research sample consisted of 230 teachers with a sampling technique using probability sampling. Research data were collected through questionnaires distributed to respondents. The research instruments were tested for validity and reliability using SPSS software to ensure the suitability of the measuring tools used.The results showed that principal leadership had a positive and significant effect on teacher performance. Work motivation also has a positive and significant effect on teacher performance and is the most dominant factor in improving teacher performance. However, principal leadership has a negative and significant effect on teacher work motivation. In addition, the mediation analysis results show that work motivation does not mediate the effect of principal leadership on teacher performance. This indicates that the effect of principal leadership on teacher performance occurs more effectively through a direct relationship.